Analis Kinerja PT. Bank Syariah Indonesia Dengan Metode Sharia Conformity And Profitability (SCNP) Dan Maqashid Sharia Index (MSI) - Hastanti Agustin Rahayu; Aniswatun Masruroh; Syarifudin Syarifudin (ITB AAS INDONESIA Surakarta, 2022)
Measurement of Islamic banking performance still using conventional methods and market penetration in Islamic banking still lag far behind conventional bank so that the Indonesian government merged the red plate Islamic bank namely BRIS, BNIS, BSM which changed their names to BSI. This study used descriptive quantitative method. The data used in this research is secondary data. Secondary data is obtained from the annual report BRIS, BNIS, BSM period 2016-2020 and BSI period 2021. Based on the data that has been obtained and the results of the analysis show that the difference in BSI performance in the 2016-2020 periode before the merger when viewed from the courtesies diagram of SCnP BRIS, BNIS, and BSM is in the same LRQ quadrant (Lower Right Quadrant) with MSI ranking results BSM ranked 1st, BRIS 2nd, and BNIS 3rd. In the 2021 period after the merger when viewed from the courtesies diagram of SCnP BSI be in the LRQ quadrant with a 4th MSI ranked. This suggests that the comparison results would be better if they had the same period i.e. before and after the merger of five years each.